Linkage of periodontitis and rheumatoid arthritis: Current evidence and potential biological interactions - de Molon, Rafael Scaf [UNESP]; Rossa, Carlos [UNESP]; Thurlings, Rogier M.; Cirelli, Joni Augusto [UNESP]; Koenders, Marije I. (MDPI, 2019)
The association between rheumatoid arthritis (RA) and periodontal disease (PD) has been the focus of numerous investigations driven by their common pathological features. RA is an autoimmune disease characterized by chronic inflammation, the production of anti-citrullinated proteins antibodies (ACPA) leading to synovial joint inflammation and destruction. PD is a chronic inflammatory condition associated with a dysbiotic microbial biofilm affecting the supporting tissues around the teeth leading to the destruction of mineralized and non-mineralized connective tissues. Chronic inflammation associated with both RA and PD is similar in the predominant adaptive immune phenotype, in the imbalance between pro- and anti-inflammatory cytokines and in the role of smoking and genetic background as risk factors. Structural damage that occurs in consequence of chronic inflammation is the ultimate cause of loss of function and disability observed with the progression of RA and PD. Interestingly, the periodontal pathogen Porphyromonas gingivalis has been implicated in the generation of ACPA in RA patients, suggesting a direct biological intersection between PD and RA. However, more studies are warranted to confirm this link, elucidate potential mechanisms involved, and ascertain temporal associations between RA and PD. This review is mainly focused on recent clinical and translational research intends to discuss and provide an overview of the relationship between RA and PD, exploring the similarities in the immune-pathological aspects and the possible mechanisms linking the development and progression of both diseases. In addition, the current available treatments targeting both RA and PD were revised.
Keywords: Alveolar bone loss; Bone; Bone resorption; Periodontal disease; Periodontitis; Rheumatoid arthritis